Vida como obra de arte: : a contemporaneidade da estetização da existência em dois atos - Alves, Lindomberto Ferreira (Revista do Colóquio, 2020)
Starting from a review of a historiographic character, this text intends to outline a general panorama of the poetic displacements in the artistic field, from antiquity to the contemporary, in order to interrogate not only the preludes to the formalization of the aesthetic dimension of life as a work of art, as well as to investigate the way in which this conception is being carried out in the field of artistic experimentation today. We will dwell on the discussion of theoretical approaches that seek to understand the origins of the crossings between art, life and work in contemporary art, especially from the analyzes carried out by the French critic Nicolas Bourriaud in “Forms of life: modern art and the invention of the self ”(2011).